Non-invasive imaging in congenital heart disease - Alonso-Gonzalez, Rafael; Swan, Lorna (SA Heart Journal, 2017)
The care of the adult patient with congenital heart disease is becoming increasingly complex. In many of these patients re-intervention, heart failure and arrhythmias are inevitable consequences of successful repair in childhood. Specialist imaging is integral to accurate diagnosis and in establishing optimal management plans for these long-term complications. Fortunately there are now a whole series of imaging techniques available to the clinician – each with its own inherent strengths and limitations. These modalities are complementary and offer fresh insight into the unique anatomy and physiology of these conditions. This paper reviews the most commonly employed imaging techniques and their contribution to assessing a patient with a congenital heart lesion.